Pengaruh Kinerja Finansial terhadap Price Book Value Perusahaan Telekomunikasi - Fahrisal, Muhammad; Sangkasari Paranita, Ekayana (Management Department, Faculty of Islamic Economics and Business, Universitas Islam Negeri Sunan Ampel Surabaya, 2024)
This research examines the effect of financial performance on stock prices, with Price Book Value as an intervening variable. The research population is telecommunications sub-industry companies listed on the Indonesia Stock Exchange in 2017-2022. The data analysis technique uses panel data regression with the Eviews 12 application. The conclusion of the first research model states that partially only the leverage and profitability ratios have a significant effect on Price Book Value. Still, simultaneously the liquidity, leverage, activity, and profitability ratio have a positive effect on Price Book Value. This finding is related to the special characteristics of the telecommunications industry which prioritizes service and trust. It is recommended that further research in the telecommunications industry add behavioral finance variables.